(untitled) (Arquivos de Ciências do Mar, 2018)
This paper gives first notiee of the. findings of Liagora mucosa Howe, Gracilarya cylindrica Borgesen, Agardhiella ramosissima (Harvey) Kylin var. dilatata J. Agardh, and Hypnea cornuta (Lamouroux) J. Agardh, along the Brazilian eoast. These speeies were previously known to oeeur at the Caribbea